Treatment of aortic dissections using a combination of the STABILISE and CERAB techniques - Technical Note - Melo,Ryan Gouveia e (2019)
Introduction: Endovascular treatment of type B aortic dissection has focused on the covering of the proximal entry tear. However, recently, concern has emerged regarding the distal aortic remodeling and new techniques such as the Stent-Assisted Balloon-Induced Intimal Disruption and Relamination (STABILISE) technique have gained more acceptance. We describe a technical note regarding the combination of the STABILISE technique in addition to the Covered Reconstruction of the Aortic Bifurcation (CERAB) technique to achieve complete aortic remodeling. Methods: The authors describe a stepwise approach regarding the endovascular repair of type B aortic dissections. A simple TEVAR is performed first. If the patient still shows signs of true lumen compression, a STABILISE technique is performed in order to achieve true lumen expansion and complete aortic remodeling. However, in some patients, false lumen perfusion and true lumen compression at the very distal aorta is maintained due to distal comunicating tears. In these patients, if there are still signs of infra-renal aortic or iliac compression/occlusion or distal thrombosis of the false lumen, a simultaneous CERAB is performed. Conclusion: By combining these techniques, we aim to cover both the proximal tear and the distal comunicating tears resulting in a complete flap apposition, false lumen obliteration, re-expansion of the true lumen and achieve optimal remodeling.